Maternal and Child Welfare at the Raleigh Fitkin Memorial Hospital and the Swazi Women’s Response, 1933-1945 (Historia, 2024)
Maternal and Child Welfare (MCW) was introduced to Swazis in 1933 by the Raleigh Fitkin Memorial (RFM) Hospital of the Church of the Nazarene (CON). Literature on its introduction shows how European doctors in colonial spaces used their knowledge of medicine to further imperial expansion and control, legitimise and maintain colonial power and undermine local belief systems. Literature on the African response to its introduction is still scanty. Drawing from archives and oral informants, this article advances the standard assumption in medical historiography of Africa which states that African people were not passive recipients of biomedical services by demonstrating that Swazi women contested and sometimes rejected some of the MCW services. The article explores overlapping interests in health care provision between the CON missionaries and the colonial government and explains why pregnancy and childbirth were shifted from the private to the public domain. Further, it investigates Swazi women’s contestation of some missionary maternal health practices, which forced CON missionaries to negotiate their uptake.
Keywords: Antenatal clinic; Church of the Nazarene; resistance; institutionalised birthing; indigenous medicine; maternal and child welfare; Raleigh Fitkin Memorial Hospital; syphilis